Akillesjänteen kierteisrakenteen kartoittaminen sekä ultraääntä ja sähköstimulaatiota yhdistävän mittausprotokollan kehittäminen - Halinen, Anu (2025)
Halinen, A. Mapping the helical structure of the Achilles tendon and developing a measurement protocol combining ultrasound and electrical stimulation. Faculty of Sport and Health Sciences, University of Jyväskylä, Master’s Thesis in Biomechanics, 63 pages, 1 appendix. The aim of this Master’s thesis was to investigate how the electrical stimulation of individual calf muscles affects the axial twisting of the Achilles tendon. The study is part of the ACHILLES project at the Faculty of Sport and Health Sciences, University of Jyväskylä, which focuses on developing the USTIM method (UltraSound and electrical STIMulation). This method combines electrical stimulation and ultrasound imaging to assess the three-dimensional twist and movement of Achilles tendon sub-tendons in vivo. A new measurement and research protocol was developed and tested in the present study. Achilles tendon injuries are common in both athletes and the general population. For example, up to 50% of competitive runners experience Achilles tendon issues during their lifetime. These injuries can cause pain, mobility limitations, and prolonged rehabilitation. The tendon’s helical structure allows for effective load tolerance, but individual structural variations may affect injury risk. A more detailed understanding of the hierarchical and helical substructures of the tendon may enhance both injury prevention and rehabilitation strategies—even in surgical contexts. In the experiment, different heads of the triceps surae (medial and lateral gastrocnemius and soleus) were stimulated, and tendon movement was imaged with ultrasound. Fourteen healthy adults (9 women, 5 men) aged 18–55 years (mean 29.86 ± 4.66 years) participated. Participants had no lower limb injuries or conditions in the previous six months. Non-parametric statistical methods were used, including Friedman’s ANOVA and the Wilcoxon signed-rank test. Statistically significant differences (p < 0.05) were observed across the eight stimulation conditions, but no pairwise differences remained significant after Bonferroni correction. Repeatability was assessed by testing one participant on two different days, with consistent response patterns observed. The protocol proved technically feasible and repeatable, although repeatability was evaluated in only one subject. Preliminary findings suggested muscle-specific differences in the tendon’s response to stimulation, although these did not reach statistical significance—possibly due to the small sample size. Nevertheless, the USTIM method showed potential for exploring internal tendon movement, and further development with a larger sample and refined stimulation is warranted. Keywords: Achilles tendon, electrical stimulation, ultrasound imaging